MAQASHID SYARIAH INDEX DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI PADA PERUSAHAAN ASURANSI SYARIAH - Puji Sahara; Titin Hartini; Sri Delasmi Jayanti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2020)
This study aims to examine the effect of maqashid syariah index, an independent board of commissioners on firm value by mediating profitability. The population in this study is sharia insurance companies listed on the Indonesia Stock Exchange. The independent variable of this study is maqashid syariah index (X1) and independent board of commissioners (X2), while the mediating variable namely profitability (Z), and the dependent variable of this study is the value of the company (Y). The method of this research uses quantitative research methods using secondary data. The sampling technique uses a purposive sample method and is based on predetermined criteria. From the sampling method applied, 11 insurance companies were listed on the Indonesia Stock Exchange (IDX) for the period of 2015 - 2018. Data analysis techniques used regression analysis and path analysis using SPSS 22. The results showed that the maqashid syariah index had an effect on profitability, the independent board of commissioners had no effect on profitability, the maqashid sharia index had no effect on firm value, the independent board of commissioners had an effect on company value, partial mediation had influence on maqashid index on firm value, profitability does not mediate the influence of the independent board of commissioners on the value of the company.